(untitled) (KYAMC Journal, 2013)
Background: Bangladesh is a country having high density of population in the world. Its fertility rate ranges from 4.1 to 5.49 and life expectancy is 66years while the total fertility rate of Asia is 2.2 and life expectancy 70 years. This study was conducted to investigate the pattern of contraceptive practices among the married women of reproductive age in the garments factory. Material and Methods: This descriptive cross sectional survey was carried out among 240 married women of reproductive age from January to June,2012 in the garments factory of Dhaka city . Data were collected on a pre-tested questionnaire by face to face interview. SPSS version 16 was used to analyzed the data. A p-value of 0.05 was considered significant for inference. Results: The mean age of the study population was 29±6.5 years with the mean age at marriage of 17.18±2.7 years. 73(31%) were practicing some methods of contraception, while 167 (69%) were not using it. OCP (Oral Contraceptive Pill) was the commonest method of contraception followed by Condoms 12(5%), Injectable 12(5%), Implant 12(5%) & Tubectomy 6(3%). None was found using IUCD and Traditional method ( withdrawal, rhythm method ) and emergency contraceptive method. The use of contraceptives were more common in grand multipara (p<0.01), >35 years old ladies (p<0.05). No statistical association was found between the use of contraceptive method and educational status of the respondents and their husband. Non users of contraceptives in this study were 167 (69%) and the major reasons for the non use were intention to have more children 53(31.46%) followed by pressure from the husband 21(12.35%), prohibition by the religion 18 (10.9%) and desire for son 17 (10.11%). Among the 73 contraceptive users 38 (52%) experienced side effects with the use of contraceptives. The commonest side effects were menstrual irregularities 17(23.8%) followed by change in body weight 8(11.19%). Conclusion: Frequency of contraceptive use was found comparatively low among garments workers despite high level of awareness. Desire for larger family, religious concerns and fear of side effects were the main factors responsible for non users. Religious scholars must play their role in clarifying many aspects regarding contraceptives. KYAMC Journal Vol. 3, No.-2, January 2013, Page 282-289 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15168